ENDOGAMOUS MARRIAGES IN THE ISOLATED MOUNTAIN OF GRADIŞTEA DE MUNTE, HUNEDOARA COUNTY (PANGEEA, 2025)
In the traditional Romanian village in the mountain area, isolation naturally leads to endogamous marital behavior. To this is added the concern for the conservation of the land property. In the interval 1824-1995 the demographic data on nuptiality demonstrate an accentuated endogamous behavior (especially until 1960). There are real family clans present to this day.
Keywords: mountain isolated; endogamy; family clans